2016
DOI: 10.18240/ijo.2016.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of axon regeneration and inhibition of astrocyte activation by alpha A-crystallin on crushed optic nerve

Abstract: Our results suggest α-crystallin promotes the axon regeneration of RGCs and suppresses the activation of astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…An important limitation of these studies is that the researchers studied co-purified aggregates containing αA- and αB-crystallins, precluding at this point a clear understanding of the relative contribution of each individual chaperone. Starting to clarify the individual roles of αA- and αB-crystallin, a recent study reported an association between αA-crystallin, inhibition of astrocyte activation, and axon elongation following optic nerve crush ( Shao et al, 2016 ). On the other hand, cell culture experiments using hippocampal neurons have shown that αB-crystallin regulates dendritic complexity, and does so in a phosphorylation-dependent manner ( Bartelt-Kirbach et al, 2016 ).…”
Section: Heat Shock Proteins Regulate Neuronal and Glial Cell Growthmentioning
confidence: 99%
“…An important limitation of these studies is that the researchers studied co-purified aggregates containing αA- and αB-crystallins, precluding at this point a clear understanding of the relative contribution of each individual chaperone. Starting to clarify the individual roles of αA- and αB-crystallin, a recent study reported an association between αA-crystallin, inhibition of astrocyte activation, and axon elongation following optic nerve crush ( Shao et al, 2016 ). On the other hand, cell culture experiments using hippocampal neurons have shown that αB-crystallin regulates dendritic complexity, and does so in a phosphorylation-dependent manner ( Bartelt-Kirbach et al, 2016 ).…”
Section: Heat Shock Proteins Regulate Neuronal and Glial Cell Growthmentioning
confidence: 99%
“…Similarly, exogenous supplementation of αA-crystallin via intravitreal injections was associated with significantly decreased levels of GFAP in both the retina and the crush site following the third day of optic nerve crush injury and induced astrocytes architecture remodeling at the crush site ( Piri et al, 2016 ). In the increased intraocular pressure model, intravitreal injection of αB-crystallin was also able to increase RGCs survival and function, as measured by functional photopic electroretinogram, retinal nerve fiber layer thickness, and RGC counts ( Shao et al, 2016 ). Another study has reported the enhanced rate of survival in the axotomized axons beyond the crush site after a single intravitreal administration of α-crystallin at the time of axotomy ( Anders et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In further experiments in this study, α-crystallin was shown to have a scavenging ability toward sulfur and nitrogen oxides. Inhibition of astrocyte activation was also demonstrated in an optic nerve crush model by intravitreal application of αA-crystallin [ 125 ]. The mechanism of neuroprotective action is not fully understood; however, recent studies showed that phosphorylation of tyrosine 148 mediates protective properties on αA-crystallin in experimental diabetic models [ 126 ].…”
Section: Therapeutical Approaches For Future Glaucoma Therapymentioning
confidence: 99%